ANALISA BIAYA OPERASIONAL KENDARAAN PADA ANGKUTAN UMUM BUS (TRAYEK PALANGKA RAYA – PANGKALAN BUN) - Ari Widya Permana; Nirwana Puspasari (Rekayasa Sipil, 2023)
Bus transportation existence in Central Kalimantan is very important because it is able to carry out mass transportation, connecting and reaching all areas of Central Kalimantan. This research was conducted to obtain the appropriate amount of vehicle operating costs and passenger fares to be applied under normal conditions and during the COVID-19 pandemic. Primary data were obtained through questionnaires, namely vehicle operating costs components data and passenger trips data. Analysis was carried out based on Decree of Transportation Minister No. KM. 89 of 2002. Vehicle operating costs per seat kilometer for the Palangka Raya – Pangkalan Bun route on the Damri Bus are IDR 131.04/seat-km, while the Logos Bus is IDR 170.97/seat-km. Under normal conditions, the Damri Bus fare is IDR 190,453/passenger, while the Logos Bus fare is IDR 134,241/passenger. During the COVID-19 pandemic, the Damri Bus fare was IDR 216,707/pnp, while the Logos bus fare was IDR 198,435/pnp.